Effect of bio-based phytate (PA-THAM) on the flame retardant and mechanical properties of polylactide (PLA) - Y. X. Yang; L. Haurie; J. Zhang; X-Q. Zhang; R. Wang; D-Y. Wang (eXPRESS Polymer Letters)
A novel bio-based flame retardant (Phytic acid – trometamol, PA-THAM) was prepared via salt formation reaction between phytic acid and trometamol. The chemical structure and thermal stability of this novel phytate were characterized by Nuclear magnetic resonance spectroscopy (NMR), Fourier transform infrared spectroscopy (FTIR), and Thermogravimetric analysis (TGA). Afterward, the effect of PA-THAM on the flammability of PLA was investigated. On the basis of the results, 3 wt% incorporation of PA-THAM in PLA exhibited better results than pure PLA in flame combustion tests, for example, LOI value increased from 19.9 to 25.8% and ratings in UL-94 varied from No Rating to V-0 rating. This ignitionresistance performance was analyzed investigating the relationship between properties and structure. The results elucidated that the incorporation of PA-THAM significantly reduced the molten viscosity of biocomposite, which facilitated the ‘heat transfer’ effect to rapidly decrease the surface temperature. In comparison with neat PLA, the same load of PA-THAM in PLA had little effect on the mechanical properties of PLA-based biocomposite, which indicated that the optimum load of PA-THAM maintained the balance of fire retardancy and mechanical properties of the PLA biocomposite.